The molecular basis of autism - Fatemi, S. Hossein, editor. (New York : Springer, 2015)
"This book is a comprehensive overview of the clinical and scientific aspects of Autism from the leading experts in the field. The clinical section covers everything from epidemiological features to epigenetic regulation to behavioral therapies and much in between. The basic science section presents the latest knowledge on the underlying causes of the disorder including the role of various neurotransmitters, neurexins and neuroligins, reelin, and other proteins. Chapters also explore the cognition and motor control in autism and the connection between oxidative stress and mitochondrial dysfunction and autism. The thorough description of these underlying causes may help researchers and clinicians find more effective treatments and therapies for the 1 in 68 American children who have been diagnosed with Autism"--Back cover.